Marketing de relacionamento: a fidelização de clientes caso Programa de Fidelidade Petrobras Premmia - Silva, Davi Gleydiston Oliveira da (2014)
The fuel market has reached soaring results each year, however, has been observed changes in the consumer profile. The research identified that current customers aspire to receive a highly personalized treatment as a result of a friendly relationship with their supplier. According to this profile of consumers, the fuel distributors have adopted the marketing strategy of offering incentives to make the customer loyal to a brand, as well as their distribution teams. In the survey, it was decided to evaluate the process of loyalty held by Petrobras Network stations through it`s Loyalty Program called Petrobras Premmia, that acts as an incentive to changes and to the process of qualifying service tool. Through the analysis of data, as a result of the research, it became apparent that the consumer market for petroleum products is accessible to improvements in the relationship process, considering the amount of customers adhesions to the Loyalty Program Petrobras Premmia in a short time. So, it seems, within the limits of accuracy of the pilot survey, that the service stations that offer additional services, regular bonuses and promotions tend to perform is a differential seen and appreciated by the consuming public.